First record of Magdalis margaritae Barrios, 1984 (Coleoptera, Curculionidae) from Altaiskii Krai and notes on Siberian elm weevils - Legalov, Andrei A. (Ecologica Montenegrina)
The first record of Magdalis margaritae Barrios, 1984 (Curculionidae: Molytinae: Magdalini) from Altaiskii Krai is given. It is the most western find of this species. The illustrations and redescription of M. margaritae are presented. The distribution maps for Siberian elm weevils, M. margaritae, Orchestes ruber (Ter-Minassian, 1953), O. steppensis Korotyaev, 2016, O. medvedevi (Korotyaev, 1995), O. mutabilis Boheman, 1843 and Anthonomus maculatus Ter Minassian, 1973 are given.